Grundtvig som tænker. Henning Højrup: Grundtvigs syn paa tro og erkendelse - Scharling, C. I. (Grundtvig-studier, 1949)
Henning Høirup: Grundtvig’s Views on Faith and Knowledge. The Principle of Contradiction as a Theological Axiom in Grundtvig's Writings. Review by C. I. Scharling. Dr. Høirup’s thesis is a contribution of the utmost significance to recent Grundtvigian research, and it is an honour for the Grundtvig Society to present this monumental work as the first of its published books. To a greater extent than any of his predecessors the author has made use of the great mass of unpublished material in the Grundtvig Archives in the Royal Library at Copenhagen. The copious extracts which Dr. Høirup gives from Grundtvig’s “ Brevveksling” (cp. Grundtvig-Studier, 1948, P. 103) show most convincingly how important it is that all the manuscripts left by Grundtvig should be published. But, above all, the value of the book lies in its success in bringing to light a completely new and unquestionably correct point of view from which to study the whole field of Grundtvig’s thought. Earlier research students have concentrated on investigating the individual presuppositions of Grundtvig’s philosophy (influences from particular philosophers such as Fichte and Schelling); Høirup considers it important to investigate also his general presuppositions, the structural contribution of the general contemporary philosophical mode of thought which he met with, for instance, in the propaedeutic instruction given at the university. Here Prof. Riisbrigh, who was a pupil of Christian Wolff, lectured on dogmatic realism, i. e., the theory that existence as it is in itself agrees with the laws of our thought. Thus the real fundamental law, not only for all thought, but also for existence, is the principle of contradiction (“ principium contradictions” ), the great “ Either— Or” , in accordance with which nothing which contradicts itself can be true, while what one cannot deny without contradicting oneself must be true. In 1813, during Grundtvig’s controversy with Schelling, H. C. Ørsted and C. Molbech, he “discovers” the principle of contradiction and uses it as a weapon against pantheism; this principle is “ the stone which shall crush the troll” (i.e., Schelling), since it proves the impossible character of Schelling’s philosophy, which attempted to abolish the opposition between evil and good and to claim that life’s great antitheses are only apparent, not real. Against Schelling’s religious monism Grundtvig sets Christian dualism, and his weapon is the principle of contradiction, “ truth’s fundamental law”. With the help of this axiom which, applied to the basis of the historical Revelation, must be the guiding light in all Christian knowledge, Grundtvig also carried on his Church controversy (beginning with “ The Church’s Reply” in 1825) against the rationalist Professor of Theology, H. N. Clausen. It is self-contradictory for Clausen to want to be regarded as a “ Protestant” while at the same time he rejects the Lutheran conception of Christianity; he holds fast to the Lutheran “ Scripture principle” (“ skriftprincip” ) while simultaneously he rejects what is acknowledged to be the Christianity of the Apostles. In opposition to this Grundtvig maintains that the proof of what is true Christianity is not primarily to be found in the Scriptures (and certainly not when they are read in isolation from the faith of the Church), but in the Church itself, in its confession of faith repeated aloud at baptism and Holy Communion, both of which are older than the Scriptures. Dr. Høirup shows in an interesting manner that Grundtvig builds up his “ view of the Church” with the help of the principle of contradiction, and how later, also with the help of this principle, he forms his peculiar theory that the Apostles’ Creed is “ the word from the Lord’s own mouth”, spoken by the risen Lord Himself to the disciples during the forty days between the Resurrection and the Ascension. While Grundtvig originally regarded the confession of faith at baptism as the witness of the Church (both the Church of the present day and the Church of the Apostles) as to what is true Christianity, he later emphasizes that the confession (i. e., the Creed) is the voice of the Church and of the Spirit blent into one; from claiming that the baptismal procedure is the Lord's own voice which creates life he goes farther and teaches that the Apostles’ Creed is historically the word of the Lord. From the principle of contradiction Grundtvig argues that there must be a common word of truth which makes the true Christian community recognisable for all; this word must be a spoken, not a written word; and it must be the confession of faith which is spoken at reception into the Church — that is, at baptism. Baptism and its conditions must have been ordained by Jesus Himself. All this series of conclusions must be true, because the opposed suppositions represent an impossibility. The theory of knowledge as a rule faithfully applied by Grundtvig to the historical Revelation and to the proceedings which are the foundation of the Church and the means of salvation gave his theology a strong evangelical basis, but also somewhat unbalanced it; it caused him to let dogma get the better of history in his dogmatic teaching about the Apostles’ Creed as the “ evangelium quadraginta dierum”. The fact that this theory of knowledge could have such great significance for Grundtvig was due partly to his antithetical, non-dialectical mode of thought, partly—and especially—to his whole philosophy of life, which is based on a conviction of the dualism of existence, the irreconcilable opposition between truth and untruth, life and death. We are all engaged in the irreconcilable conflict that exists between the God of truth and the father of lies: “ We must deny one of the two, God or Satan.” Therefore Grundtvig finds the central point of the Christian life precisely in the combination of renunciation and confession of faith at baptism. Through this knitting together of renunciation and faith baptism becomes “ the living expression” of the principle of contradiction. Dr. Høirup’s treatise also provides a thorough discussion of Grundtvig’s whole conception of the relation between faith and knowledge, his “ Christian logic”, i. e. theory of knowledge. In spite of all the influence which Wolff’s methods of proof had upon him, Grundtvig decidedly dissociates himself from the rationalist theory of knowledge because it isolates knowledge both from faith and from the other psychological faculties: feeling and imagination. Grundtvig constantly maintains that philosophy by itself cannot construct a system of metaphysics, and that certainty of faith cannot be attained by logic. “ When human reason regards itself as pure reason and truth itself and seeks to develop the truth out of itself, it is the servant of falsehood,” he thunders against Schelling. But he is willing to recognise to the full the importance of reason when it is obedient to faith in the [divine] revelation. On the other hand, knowledge becomes barren if it is not combined with feeling and images (the faculty of imagination) ; this leads to a warm defence of the rights of the knowledge conveyed through poetic imagery and therewith of the symbolic language of the Bible (see P. 104 and 216 f. of Høirup’s book). According to Grundtvig, true Christian knowledge is bound up with experience, history and revelation. Dr. Høirup fully and fruitfully discusses Grundtvig’s contribution as a theological thinker in these spheres. One of the most outstanding sections of the treatise is the detailed examination of Grundtvig’s relation to Locke (P. 137 ff.), where he shows that English philosophy with its emphasis on empiricism taught Grundtvig that experience is “ the source of all knowledge”. But experience for Grundtvig means above all the experience of the human race — that is, history. The determination of what is true Christianity must be reached by the way of history. Christian knowledge is decisively bound up with revelation; in contrast to the “ riddling speech” of the myths, the historical Christian revelation is made known in the Word which must be accepted as it is spoken. Grundtvig’s conception of revelation is not a static intellectual one, but dynamic; God reveals Himself in history, as acting to achieve our salvation, and God reveals Himself continually by the activity of the Son and the Holy Spirit; therefore the evidence of God’s revelation must be sought first of all in the living Church, whose Creed and sacraments are the norm for the correct interpretation of the Bible. The central significance of Dr. Høirup’s book lies in its historical research. Opinions will always be divided as to the systematic justification of Grundtvig’s view; Dr. Høirup agrees in the main with Grundtvig’s view of the Church & the sacraments, but clearly dissociates himself from the “ divagation” in his special doctrine about the Creed. It is Dr. Høirup’s great merit that by his thorough research he h...